Examining preconception care-related knowledge and attitudes among Chinese immigrants in Canada. Issue 1 (6th March 2017) - Teng, Jing; Ahmed, Rukhsana
Abstract : Purpose: The purpose of this paper is to examine knowledge and attitudes about preconception health care among Chinese immigrants in Canada. Design/methodology/approach: A cross-sectional internet-based survey, informed by the principles of the health belief model, was administered to a convenience sample in Ottawa, Canada. In total, 76 respondents from the Chinese community participated in the online survey. Findings: Overall, participants demonstrated: low to moderate awareness of preconception related risk factors and preconception health; neutral to slightly positive attitudes toward carrying out preconception care; considerable confusion over the differences among preconception care, premarital health care (Mainland China), and prenatal health care; great sensitivity to subjective norms related to spouses, parents, and friends; and a strong desire for receiving information and communication from health care professionals. Practical implications: An emphasis on reducing misperceptions and offering information about the preconception period and potential severe pregnancy-related risks may contribute to a better knowledge and intended behavior toward preconception care among Chinese immigrants, and ultimately optimize both their reproductive health and their future children's health. Originality/value: The cultural norms and population policies in the sending country may frame immigrants' knowledge and attitudes related to preconception health care. This study fills the gap in the literature regarding Chinese immigrants' knowledge levels and attitudes toward preconception care in Canada and thus offers insights into how to deliver culturally competent care and design effective communication strategies to reach out to ethnocultural communities.